Impact of Renin–Angiotensin–Aldosterone System (RAAS) Gene Polymorphism in Essential Hypertension and Antihypertensive Drug Therapy: A Review - Archana Adhikari; Chandrakala Sharma; Mingma Lhamu Sherpa; Gauthaman Karaunakran; Mona Dhakal; Anita Sharma (International Journal of Hypertension)
Genetic, demographic and environmental factors all play a role in the frequency of an intricate multifactorial condition known as hypertension. Approximately 30% and 50% of BP fluctuation are influenced by genetic variability. Many genetic studies have confirmed the link between genetic variability and susceptibility to essential hypertension; hence, identifying genes associated with essential hypertension susceptibility will aid in understanding the pathophysiology and their influence on how an individual responds towards the antihypertensive therapy. There are also controversial results highlighted in some reports. This review summarises genetic variants of the renin–angiotensin–aldosterone system (RAAS), angiotensinogen (AGT) (M235T), angiotensin converting enzyme (ACE) (insertion/deletion), angiotensin II type 1 receptor (AT1R) (A1166C) and aldosterone synthase (C344T) that are known and might contribute towards the pathophysiology of essential hypertension. Furthermore, the review highlights the response of certain RAAS gene polymorphisms (renin, ACE and AT1R genes) to antihypertensive drugs.